Integrating Co3O4 nanocubes on MXene anchored CFE for improved electrocatalytic activity: Freestanding flexible electrode for glucose sensing. Issue 5 (October 2022) - Manoj, Devarajan; Aziz, Ayesha; Muhammad, Nadeem; Wang, Zhanpeng; Xiao, Fei; Asif, Muhammad; Sun, Yimin
Abstract: Developing facile strategies to construct free-standing flexible electrodes with extremely sensitive and stable electrochemical response towards analytes is of huge demand and it is still highly challenging. Herein, we design a unique and cost-effective hybrid electrode comprising of cobalt oxide (Co3 O4 ) directly grown on highly conducting MXene based carbon fiber electrode (CFE) as a self-standing electrode using a simple hydrothermal-annealing method, where MXene nanosheets on electrode support facilitate the growth of uniform-sized Co3 O4 nanocubes. Our results demonstrate that the synergetic effects of conductive MXene support and catalytically active Co3 O4 nanocubes provide a superior response towards glucose oxidation in an alkaline medium (0.1 M KOH). The resultant Co3 O4 /MXene@CFE demonstrates remarkable sensitivity (19.3 μA mM −1 cm −2 ), wide linear range (0.05 μM to 7.44 mM) and lower detection limits (10 nM), thus providing excellent selectivity over interfering species and good electrochemical stability for an extended shelf-life. Therefore, the obtained self-standing Co3 O4 /MXene@CFE flexible electrode establishes a promising platform for glucose oxidation and it could be envisioned for the highly sensitive detection of various target molecules for their widespread applications in clinical diagnosis and health care monitoring. Graphical Abstract: Schematic representing the working principle of Co3 O4 /MXene@CFE based for electrochemical sensor for glucose detection from real samples. ga1 Highlights: Successful integration of Co3 O4 nanocubes on MXene anchored CFE. Simple hydrothermal-annealing method is used to fabricate freestanding Co3 O4 /MXene@CFE. The Co3 O4 /MXene@CFE displays enhanced electrochemical sensing performance for glucose detection. The sensor has been successfully applied to determine glucose in human serum samples.